Resistive switching effect on Al2O3/InGaAs stacks - Palumbo, Félix Roberto Mario (2013)
The resistive switching (RS) pheno menon is currently attracting a lot of attention due to its potential Applicability for nonvolatile memory devices. Among all the systems currently under consideration, the analysis of MG/Al2O3/InGaAs is very relevant since this stack is a strong candidate for the new generation of CMOS devices with high mobility channels